(untitled) - Block, Peter (San Francisco, 1987)
Peter Block, the author of the classic Flawless Consulting, is a true visionary. And here he turns his sights on management. Managers and other employees who feel powerless to control their own destinies, who feel stifled by bureaucracy, who feel sapped of creativity--will feel invigorated by Block's legAndary insight. Offers practical advice to help your managers: Empower themselves to help shape the organization, Develop positive political skills in their dealings with all levels of employees,...
Keywords: Organizational behavior,Organizational effectiveness,Office politics,Executive ability